The Presence of the Saint in Popular Belief in the Djelfa Region: Between Reality and Myth – A Reading of Selected Poetic Samples - rezigui, hadjsaad; djadi, Amar (El Omda in Linguistics and Discourse Analysis, 2025)
The popular thought of the Djelfa region, like others, was influenced by the belief of the saint, and this was reflected in the popular belief of the Gilfawi community, and the translation of the popular poets, which circulated in the thoughts of the public, suddenly their poems were filled with the praise of the saints, and their exaggeration sometimes reached the point where they elevated these people from the human world to the ranks of the gods and from reality To the legend, and in the light of this study, we will reveal the extent of the popular poet's attachment to the idea of the saint based on poetic models born from the environment